Study of the tectonic and the volcanicity in the North Tanzania Divergence area (South Ending of the Kenya Rift). Petrological and geochemical characteristics of recent volcanism (0 – 8 My) and mantle sources. New constraints on the geodynamical environment. - (:unkn) unknown (My University, 2007)
The East African Rift System (EARS) is the best example worldwide of an active magmatic rift. It extends over more than 3500 km from the Afar province to the Mozambican Gulf, cutting through the Ethiopian and East Africa elevated plateaus that are the topographic expression of one or several Cenozoic mantle plumes beneath this part of Africa. Extensional strain initited along the eastern magmatic branch of the EARS at ca. 30 My in the Afar, and then propagated southwards by linkage of discrete magmatic cells centered on the Kenyan dome, to reach South Kenya 8 My ago. There, the North Tanzanian Divergence (NTD) corresponds to a dramatic change in structural style, associated with the abrupt disappearance of magmatism southwards. The transition zone from the NS axial valley into three diverging rift arms (Eyasi, Natron-Manyara and Pangani), dominated by tilted basement fault blocks, is outlined by a 200 km-long transverse volcanic chain, including major Neogene volcanic edifices such as the Ngorongoro, Mount Meru and Kilimanjaro. Our work presents new structural and geochemical results on magmatic rocks in the NTD, and its main originality is to integrate complementary approaches involving field investigations, petrological-mineralogical analyses, geochronology, Sr-Nd isotopic and trace elements geochemistry. That allows us to also precise the build-up history and mechanisms of a number of major volcanoes of the NTD (Ngorongoro, Mount Meru, Kilimanjaro) during Plio-Quaternary times. Applying this approach to a wider scale, and compiling published radiometric data with our own K-Ar age determinations, allows us to establish a kinematic rift propagation model to the NTD for the last 8 My. It is proposed that both magmatism and strain shifted eastwards along the transverse volcanic chain, up to the Pangani arm, from 8 My to Present, with the onset of magmatic activity in the whole NTD at 2.5 My. But, the main contribution of our study is
Keywords: African Research